The analysis of grid independence study in continuous disperse of MQL delivery system - Z., Zulkifli; N. H., Abdul Halim; Z. H., Solihin; J., Saedon; A. A., Ahmad; A. H., Abdullah; N., Abdul Raof; Musfirah, Abdul Hadi (Faculty Mechanical Engineering, UMP, 2023)
A sustainable cutting method of Minimum Quantity Lubricant (MQL) was introduced to promote lubrication effect and improve machinability. However, its performances are very dependent on the effectiveness of its mist to penetrate deep into the cutting zone. Optimizing the MQL system requires massive experimental work that increases cost and time. Therefore, this study conducts Computational Fluid Dynamic (CFD) analysis using ANSYS Fluent and focuses on the grid independence study in dispersed-continuous phase of MQL delivery system. The main aim is to identify the best mesh model that influences the accuracy of the CFD model. The analysis proposed two different unstructured grid cell elements of quadrilateral and triangular that were only applicable for 2-dimensional fluid flow in CFD. The unstructured grid was controlled with three different mesh quality factors such as Relevance Center, Smoothing, and Span Angle Center at coarse /low, medium, and fine /high. The results showed that the best mesh quality for quadrilateral was at 60,000 nodes number and coarse mesh, whereas the triangular was at 90,000 nodes number and coarse mesh. Both combinations resulted the most consistent and reliable result when compared with past studies. However, this study decided to choose quadrilateral cell element with 60,000 nodes number and coarse mesh as it is considered to be sufficient to provide accurate and reliable result as well as practical in terms of computational time for the MQL model in CFD analysis.